STUDENTS’ PERCEPTIONS TOWARD GAMIFICATION APPLIED IN ENGLISH LANGUAGE EDUCATION FBS UNM - Samanta, Samanta; Jabu, Baso; Sakkir, Geminastiti (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This qualitative study explores students' perceptions of gamification, a strategy incorporating game-like elements into education, to understand its impact on contemporary learning. The objective is to assess whether students view gamification as a positive or negative tool for learning in the classroom. Five students with prior experience using gamification participated in the study, selected through purposive sampling. The primary method of data collection was in-depth interviews. Findings indicate that students generally perceive gamification positively. Benefits noted include increased enjoyment and interactivity in learning, enhanced motivation and competitive spirit, and the development of critical thinking, problem-solving, and collaboration skills. However, the study also identifies several challenges associated with gamification, namely technical and accessibility issues, potential reduction in personal interaction, an overemphasis on competition, and distractions from educational objectives.